Dampak Penjaminan Mutu Eksternal di Perguruan Tinggi - Anindita Rossa Herdyaningrum; Faiz Muzakki (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Accreditation serves as a measurement of the eligibility of educational programs against predetermined criteria. This study analyzes the effectiveness of accreditation assessment instruments in enhancing school performance. Based on National Education Standards, the accreditation instrument functions as an evaluation tool to assess the quality and eligibility of educational institutions. Utilizing a qualitative approach through literature review, the findings indicate that the accreditation instrument effectively provides a comprehensive overview of school performance, encompassing aspects of learning, management, and facilities. This tool aids in identifying strengths and weaknesses, guiding the development of sustainable improvement strategies. The study concludes that the accreditation assessment instrument is not merely an evaluative tool but also a catalyst for the overall enhancement of school performance.